Media Interview Skills - Ricky Telg (EDIS)
Believe it or not, if you know what you want to say and have confidence in your ability and appearance, an interview can be a rewarding and enjoyable experience. This 4-page fact sheet focuses on basic media interview skills to help you feel comfortable during an interview. Written by Ricky Telg and published by the UF Department of Agricultural Education and Communication, August 2011. (UF/IFAS Photo by Tyler Jones)